2012
DOI: 10.1186/1471-2164-13-398
|View full text |Cite
|
Sign up to set email alerts
|

A physical map of a BAC clone contig covering the entire autosome insertion between ovine MHC Class IIa and IIb

Abstract: BackgroundThe ovine Major Histocompatibility Complex (MHC) harbors genes involved in overall resistance/susceptibility of the host to infectious diseases. Compared to human and mouse, the ovine MHC is interrupted by a large piece of autosome insertion via a hypothetical chromosome inversion that constitutes ~25% of ovine chromosome 20. The evolutionary consequence of such an inversion and an insertion (inversion/insertion) in relation to MHC function remains unknown. We previously constructed a BAC clone physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This hypothesis of ancestral chromosome rearrangement in ruminants has been supported by previous studies comparing the MHC sequences of cattle and sheep with those of nonruminants (such as humans, chimpanzees, and mice) (11,58). Considering that subfamily Hippotraginae is phylogenetically most distant from subfamily Caprinae Bovinae in the family Bovidae ( Figure S7), our results proposed that, at least in the Bovidae, an inversion in the MHC class II region divided the MHC class II region into two discontinuous subregions.…”
Section: Additional Evidence For the Hypothesis Of Ancestral Chromososupporting
confidence: 84%
See 1 more Smart Citation
“…This hypothesis of ancestral chromosome rearrangement in ruminants has been supported by previous studies comparing the MHC sequences of cattle and sheep with those of nonruminants (such as humans, chimpanzees, and mice) (11,58). Considering that subfamily Hippotraginae is phylogenetically most distant from subfamily Caprinae Bovinae in the family Bovidae ( Figure S7), our results proposed that, at least in the Bovidae, an inversion in the MHC class II region divided the MHC class II region into two discontinuous subregions.…”
Section: Additional Evidence For the Hypothesis Of Ancestral Chromososupporting
confidence: 84%
“…The genomic organization of MHC in mammals is relatively conserved, with a basic orientation of class I, class III, and class II (9). However, distinct from other animals, the MHC class II region in sheep and cattle is composed of two discontinuous regions, class IIa and class IIb, which result from a substantial autosome inversion (10,11). Recent studies have indicated that this chromosome inversion was also found in the Yangtze porpoise, killer whale, and seven other cetaceans (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…(2) MHC organization and usage have noticeable difference from humans. Bovids have an MHC gene organization not seen in other mammals whereby the class II region of the MHC is divided into MHC IIa and MHC IIb regions (148,149). Further, domestic cattle can often express 1-6 different MHC genes, demonstrating plasticity in MHC expression (150).…”
Section: Co-infectionsmentioning
confidence: 99%
“…Until now, in no other higher primate has the MHC been sequenced and analysed to the same depth as the human, so this study of such a close ancestor should prove a valuable resource that can be expected to advance our understanding of the structure, function, variation and evolution of this complex region in primates. It also adds to the growing body of data on MHC genes and regions (74) in vertebrates in general (75–78). …”
Section: Resultsmentioning
confidence: 99%